Pengaruh Kompetensi Project Manager Terhadap Keberhasilan Proyek Konstruksi Gedung di Banda Aceh dan Aceh Besar - Mastura, Cut Annisa Widya Sari; Buraida, Buraida; Nurisra, Nurisra; Tari, Jihan Fardila (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
The construction sector is a major pillar of development and continues to grow across regions. Project success is strongly influenced by human resource quality, particularly the managerial competence of the project manager. This competence includes knowledge, skills, and attitude, which ensure that projects are completed on budget, on quality, and on schedule. However, field conditions still show gaps, such as the appointment of project managers without sufficient capacity, leading to delays, cost overruns, and quality issues. This study examines the influence of project manager competence on the success of building construction projects in Banda Aceh and Aceh Besar. The research approach uses a qualitative method with a descriptive approach. Data were collected through questionnaires distributed to contractors and supervising consultants, involving 35 respondents. The independent variables are knowledge (X1), skill (X2), and attitude (X3), while the dependent variable is project success (Y). The results show that all three competency variables significantly affect project success, indicated by an F-test value of 0.018 (< 0.05). The regression equation is Y = 14.105 + 0.152X1 + 0.139X2 + 0.178X3. The R² value of 0.272 shows that 27.2% of project success is influenced by project manager competence. The study highlights the importance of improving competence, especially attitude as the most dominant factor.